The risk of non-union per fracture: current myths and revised figures from a population of over 4 million adults - Mills, Leanora A; Aitken, Stuart A; Simpson, A Hamish R W (Acta orthopaedica, 2017)
Background and purpose - Fracture non-union remains a major clinical problem, yet there are no data available regarding the overall risk of fractures progressing to non-union in a large population. We investigated the rate of non-union per fracture in a large adult population. Methods - National data collected prospectively over a 5-year period and involving just under 5,000 non-unions were analyzed and compared to the incidence of fracture in the same period. Results and interpretation - The overall risk of non-union per fracture was 1.9%, which is considerably less than previously believed. However, for certain fractures in specific age groups the risk of non-union rose to 9%. As expected, these higher rates of non-union were observed with tibial and clavicular fractures, but-less expectedly-it was in the young and middle-aged adults rather than in the older and elderly population. This study is the first to examine fracture non-union rates in a large population according to age and site, and provides more robust (and lower) estimates of non-union risk than those that are frequently quoted.